Moral and ethical considerations of early tracheostomy for patients with complete high cervical spinal cord injuries - L Erin Miller; Jennifer J Misenhimer; Luke T Sabal; John M Green (Trauma Surgery & Acute Care Open)
Cervical spinal cord injuries (SCIs) are accompanied by significant physiologic challenges as well as psychologic burdens. Patient with high cervical SCI face severe physical disability and daily medical needs, which may include long-term mechanical ventilation. Given the substantial change in quality of life, it is crucial to include such patients in early goals of care discussions, when possible. Although there exists a depth of literature considering the medical benefits of early tracheostomy for patients with cervical SCI, there is a paucity of discussion regarding the ethical considerations. With an improved ability to communicate, early tracheostomy may improve subjective quality of life and augment the patient’s sense of autonomy. Using a framework guided by the principles of medical ethics, we aim to emphasize the role of early tracheostomy for patients with high cervical SCI with a review of current literature and a case presentation from our institution.